(untitled) (Conference Zone, 2022)
The main phosphate raw materials in the Republic are phosphorites of the Central Kyzylkum. The resulting phosphoric acid from the washed calcined phosphate concentrate is mainly used to obtain phosphoruscontaining fertilizers [1]. Despite the not sore need for pure salts of phosphoric acid, they are produced in the republic in limited quantities.